Diagnostic of Innovations and Volatility Persistence in Emerging Markets - Metadjer, Widad; Benbakhti, Seyf Eddine; Boulila, Hadjer (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2020)
This paper aims to analyse the shocks and volatility persistence of both Islamic and conventional financial market, and the nature of the correlation between the two markets. The study uses Bivariate BEKK-GARCH(1,1) model in the examination of the shocks and volatility based on the daily prices of Dubai Islamic Capital Market (Sukuk index) and conventional Stock Market (DFM index).As a result, it documents that both Sukuk and stock market indices are affected by their own news and shows volatility persistence over the study period. The study also finds a negative correlation between the Sukuk and Stock market prices during the Dubai debt crisis which indicates that Islamic bonds are good portfolio diversifier. Our study seeks to define the nature of the correlation between the Sukuk market and the stock market using daily prices, unlike other studies that use returns. In addition, our empirical results might be valuable for investors and market makers to ensure a good portfolio diversification strategy.